Critical Incidents in Pre-Service Teachers’ Beliefs and Motivation to Become English Teachers: A Study of Teacher Professional Identity Construction - Jennifer Jennifer; Concilianus Laos Mbato (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
Personal journeys in teacher education programs are crucial in helping pre-service teachers to build “a strong and positive professional identity” (Ivanova & Skara-Mincne, 2016; Yuan & Lee, 2015). This study aimed to elaborate on critical incidents regarding beliefs and motivation to become teachers in shaping teacher professional identity. It involved pre-service teachers who major in a Master’s Program in English Education at a university in Yogyakarta, Indonesia. As the methodology to collect data, critical incident techniques was used, which constitute five steps: 1) Establishing general aims; 2) Establishing plans and specifications (formulating frames of references and categories); 3) Collecting data; 4) Analyzing data; and 5) Interpreting, analyzing, and reporting data (Hughes, Williamson, & Lloyd, 2007). Some teachers may mix their experiences with blind judgments due to emotional reactions. Thus, critical incident technique enables pre-service teachers to revisit their incidents critically. The results of the study led to a conclusion that lack of personal connections between the participants and people who had taught them contributed to the participants’ neutral beliefs about teaching, which in turn contributed to their low intrinsic motivation to be teachers.